1976
DOI: 10.1152/ajplegacy.1976.231.2.283
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of renal peritubular capillaries to neutral dextrans dextrans and endogenous albumin

Abstract: Renal lymph-to-renal vein concentration ratios (CL/CV) for neutral dextrans (18-42 A effective radii) and endogenous serum albumin were measured in rats before and during acute colume expansion with isoncotic plasma or Ringer solution. Under all conditions studied, CL/CV decreased with increasing dextran size, in normal hydropenia falling from 0.93 +/- 0.03 SE at 18 A to 0.24 +/- 0.02 a 42 A (n = 12). Albumin (36 A pradius) behaved in a manner similar to a 40 A dextran, CL/CV averaging 0.33 +/- 0.03 (n = 12) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 0 publications
4
10
0
Order By: Relevance
“…SNGFR increased in each animal (Fig. 1 ' Increase in CA has also been observed after isoncotic plasma infusion in previous studies (14,40). It is speculated that this increase in systemic plasma protein concentration reflects high intracapillary hydraulic pressure in peripheral capillary during plasma volume expansion, presumably causing extravasation of colloid-free fluid.…”
Section: Resultssupporting
confidence: 64%
“…SNGFR increased in each animal (Fig. 1 ' Increase in CA has also been observed after isoncotic plasma infusion in previous studies (14,40). It is speculated that this increase in systemic plasma protein concentration reflects high intracapillary hydraulic pressure in peripheral capillary during plasma volume expansion, presumably causing extravasation of colloid-free fluid.…”
Section: Resultssupporting
confidence: 64%
“…For renal lymph, a, = 1.89 and a2 = 0.469 (for 0 _ C _ 2 g/dl), assuming an A/G of 2.0, the ratio also found in rats by us and others (21,22 …”
Section: Calculationssupporting
confidence: 75%
“…where a, = 1.63 and a2 = 0.249 (for 4 _ C ' 10 g/dl) for plasmas, assuming an albumin-to-globulin concentration ratio (A/G) of 1.0, the ratio found in normal rats by us and others (20)(21)(22). For renal lymph, a, = 1.89 and a2 = 0.469 (for 0 _ C _ 2 g/dl), assuming an A/G of 2.0, the ratio also found in rats by us and others (21,22 …”
Section: Calculationsmentioning
confidence: 90%
“…This rate is simply the cortical lymph flow, as estimated from measured flow rates, divided by the total lymphatic endothelial surface area contained in the cortex. The cortical lymph flow is estimated to be 1.0 pl/min/gm renal cortex or about 75% of the total renal lymph flow of 1.4 pl/min/gm kidney (Deen et al, 1976), since cortical lymphatics represent about 75% of total intrarenal lymphatic surface area (O'Morchoe et al, 1982). Additionally, Wolgast et al (1981) found that the cortex is about 70% of the total renal weight in rats.…”
Section: Discussionmentioning
confidence: 99%